Le système monétaire européen à la lumière de l’expérience et de la théorie monétaires - Dehem, Roger (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
In the light of monetary experience and theory, the EMS appears to be unsustainable. Monetary history of the past sixty years shows that every attempt to stabilise the international monetary System has been frustrated as a consequence of divergent egocentric monetary policies. The breakdown of the rules of the gold standard game in the twenties, as well as the use of money as an instrument in national macroeconomic policies under the Bretton Woods regime have ultimately led to the demise of the fixed exchange rates System. In the sixties, European views on monetary policies were quite divergent, but in the seventies institutional attempts were made to bring them apparently into line. The "snake" arrangements, initiated in 1972, soon degenerated. The more ambitious attempt of 1979, the institutionally more elaborate EMS, suffers from the same basic weakness as all the previous ones. It lacks a common monetary standard, such as the one proposed in the 1975 Ail-Saints Manifesto. Such a standard is a necessary and a sufficient condition for a sustainable common monetary System.